PARENTS AND TEACHERS' GIT TO PRODUCE CHARACTER OF EARLY CHILDHOOD IN RAUDHATUL ATHFAL - Putri, Al-Miftah Diyana; Latifah, Titin; Heldanita, Heldanita; AH, Nurkamelia Mukhtar; Nurhayati, Nurhayati (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
The principles of parenting related to character development, including exemplary, togetherness in realizing moral values, democratic behavior, honesty, the ability to appreciate children's development and unity of words and actions. The original purpose of this study was to determine the role of parents in the formation of children's character in RA. Al-Miftah, knowing the conflicts that parents face in making children's characters and revealing the consequences of the role of parents on the character of early childhood. as a result of interviews using a group B teacher to be a class teacher at RA. the teacher of group B stated that the students were conducted by class teachers and accompanying teachers. Assistant teachers are assigned to identify children with special needs in care. Identification of learning needs is carried out using an exclusive plunge into the field, delivering instruments and guidance. Based on the data that has been observed by researchers regarding the role of parents in shaping the character of their students, most of the parents answered that they often guided 6 people (60%), who answered that they often guided their children as much as 4 people (40%), and those who answered do not guide their children. there are no children (0%), then the conclusion of the respondents regarding the involvement of parents in the formation of the character of students is very good.